The role of the family in the rehabilitation of persons brainstem stroke - case study - Kozieł vel Kozłowska, Anna; Kwolek, Andrzej (European Journal of Clinical and Experimental Medicine, 2009)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The case of a 34-year-old woman, wife and mother of two children, who had suffered a severe stroke, was presented. Brain stem hemorrhage following basilar artery embolism. The patient stayed for several weeks in severe general condition. The stroke left the patient with serious deficits, in particular: left act, significant paresis of the right limbs, lack of body posture control, unpaired movements of the knuckles eyes, dysarthria speech. In reaction to the situation, the mental state of the patient. After staying in hospital for over six months, despite the persistence of a significant disability movement, the patient returned home, where the rehabilitation process is still actively continued. The patient was hospitalized twice in the rehabilitation ward, where further the law of her state. The family is a solid support and motivation for the patient, thanks to which she constantly undertakes toil associated with rehabilitation treatments. Thanks to continuous, intensive rehabilitation, there is a constant walks in basic functions.